Gradient structure composite material and preparation method and application thereof

Through alternate lamination and hot pressing of magnesium alloy plate and polylactic acid plate, composite materials with gradient structure were prepared, which solved the problem of insufficient hardness and wear resistance of oral restoration materials in the prior art, and realized the field of oral restoration Excellent biocompatibility and mechanical properties, suitable for complex teeth chewing environments.

CN119238970APending Publication Date: 2025-01-03BAISI BORUI MEDICAL TECH (SUZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411369411.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing oral restoration materials have shortcomings in hardness, flexibility, wear resistance and simulated teeth's natural gradient structure, which is difficult to meet the pressure distribution needs during teeth chewing, increasing the risk of tooth fracture.

Method used

The magnesium alloy plate and polylactic acid plate are alternately laminated, preheating and hot pressing treatment are performed to prepare composite materials with gradient structures. By controlling the number of stacked layers and the hot pressing conditions, the good combination of the magnesium alloy plate and polylactic acid plate is achieved. Form a composite material with excellent biocompatibility and mechanical properties.

Benefits of technology

The prepared gradient structure composite material has excellent biocompatibility and mechanical properties, suitable for oral restoration, can provide different mechanical properties in different areas, reduce tooth stress concentration, and provide a new material choice.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119238970A_ABST
    Figure CN119238970A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mouth rehabilitation, and provides a gradient structure composite material and a preparation method and application thereof. The method comprises the following steps: alternately laminating magnesium alloy plates and polylactic acid plates to obtain laminated plates; the number of layers of the laminated plate is 2n + 1, and n is an odd number greater than or equal to 1; the first layer and the (2n + 1) th layer of the laminated plate are polylactic acid plates, and the (n + 1) th layer of the laminated plate is a magnesium alloy plate; and the laminated plate is sequentially subjected to preheating treatment and hot pressing treatment, and the gradient structure composite material is obtained. The magnesium plate and the PLA are adopted as raw materials, compounding of a gradient structure is achieved through the hot pressing technology, and the obtained composite material has excellent biocompatibility and mechanical performance and is particularly suitable for the field of oral cavity restoration. According to the preparation method disclosed by the invention, by accurately controlling hot pressing conditions, good combination between the magnesium plate and the polylactic acid plate is realized, the composite material with gradient mechanical properties is prepared, and a new material choice is provided for mouth rehabilitation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oral restoration, and in particular to a gradient structure composite material and a preparation method and application thereof. Background Art

[0002] In the field of oral restoration, it is crucial to choose the right materials, because they not only affect the beauty and function of the restoration, but are also directly related to the patient's oral health and comfort. Currently, the most commonly used oral restoration materials include metal alloys, ceramics, and composite resins. Among them, metal alloys have high strength and hardness, but lack sufficient flexibility, which may cause the restoration to be inconsistent with the surrounding teeth and increase the risk of tooth fracture; although ceramic materials are similar to teeth in appearance and hardness, they are more brittle and difficult to withstand complex chewing forces; traditional composite resin materials may be closer to teeth in hardness and elasticity, but are generally not as good as ceramics and metal alloys in wear resistance and long-term stability. In addition, these materials also have limitations in simulating the natural gradient structure of teeth, which is crucial for the distribution of pressure during chewing and can effectively reduce stress concentration and potential damage to teeth.

[0003] Therefore, it is of great significance to provide an oral restoration material with excellent comprehensive performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a gradient structure composite material and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a gradient structure composite material, comprising the following steps:

[0007] Alternately stacking magnesium alloy plates and polylactic acid plates to obtain a laminated plate;

[0008] The number of layers of the laminate is 2n+1, n≥1 and n is an odd number;

[0009] The first layer and the 2n+1 layer of the laminated plate are both polylactic acid plates, and the n+1 layer of the laminated plate is a magnesium alloy plate;

[0010] The laminated plates are subjected to preheating treatment and hot pressing treatment in sequence to obtain the gradient structure composite material.

[0011] Preferably, the magnesium alloy plate includes an AZ31 magnesium alloy plate, a ZK60 magnesium alloy plate or a WE43 magnesium alloy plate.

[0012] Preferably, the magnesium alloy plate is surface treated before lamination; the surface treatment method is fluorination treatment, micro-arc oxidation treatment or anodizing treatment.

[0013] Preferably, the molecular weight of the polylactic acid in the polylactic acid board is ≥100 kDa.

[0014] Preferably, the thickness of the laminated plate decreases from the n+1th layer to the 1st layer or the 2n+1th layer, and the total thickness of the laminated plate is ≤1.2 mm.

[0015] Preferably, the ratio of the total thickness of the magnesium alloy plates used in the laminated plate to the total thickness of the polylactic acid plates used in the laminated plate is 1:1-2.

[0016] Preferably, the preheating treatment temperature is 110-130° C., and the preheating treatment time is 5-10 min.

[0017] Preferably, the temperature of the hot pressing treatment is 150-180° C., the pressure of the hot pressing treatment is 3-5 MPa, and the time of the hot pressing treatment is 10-15 min.

[0018] The present invention also provides a gradient structure composite material prepared by the preparation method of the gradient structure composite material.

[0019] The invention also provides application of the gradient structure composite material in preparing oral repair materials.

[0020] The beneficial effects of the present invention are:

[0021] The present invention provides a preparation method of a gradient structure composite material, comprising the following steps: alternately stacking magnesium alloy plates and polylactic acid plates to obtain a laminated plate; the number of layers of the laminated plate is 2n+1, n≥1 and n is an odd number; the first layer and the 2n+1 layer of the laminated plate are both polylactic acid plates, and the n+1 layer of the laminated plate is a magnesium alloy plate; the laminated plate is sequentially preheated and hot-pressed to obtain a gradient structure composite material. The present invention uses magnesium plates and PLA as raw materials, and realizes the composite of gradient structure through a hot pressing process. The obtained composite material has excellent biocompatibility and mechanical properties, and is particularly suitable for the field of oral repair. In addition, the present invention achieves a good combination between magnesium plates and polylactic acid plates by precisely controlling the hot pressing conditions, and prepares a composite material with gradient mechanical properties, which provides a new material selection for oral repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the structure of the gradient structure composite material in the present invention; Figure 1 Among them, 1 is a polylactic acid plate, and 2 is a magnesium alloy plate;

[0023] Figure 2is a bending stress-strain curve diagram of the gradient structure composite material in Examples 1 to 3; Figure 2 In Chinese, Strain means strain and Stress means pressure. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a gradient structure composite material, comprising the following steps:

[0025] Alternately stacking magnesium alloy plates and polylactic acid plates to obtain a laminated plate;

[0026] The number of layers of the laminate is 2n+1, n≥1 and n is an odd number;

[0027] The first layer and the 2n+1 layer of the laminated plate are both polylactic acid plates, and the n+1 layer of the laminated plate is a magnesium alloy plate;

[0028] The laminated plates are subjected to preheating treatment and hot pressing treatment in sequence to obtain the gradient structure composite material.

[0029] In the present invention, n≥1 and n is an odd number, preferably 1 or 3.

[0030] In the present invention, the magnesium alloy sheet preferably includes an AZ31 magnesium alloy sheet, a ZK60 magnesium alloy sheet or a WE43 magnesium alloy sheet.

[0031] In the present invention, the magnesium alloy plate is preferably surface treated before lamination; the surface treatment method is preferably fluorination treatment, micro-arc oxidation treatment or anodizing treatment; the fluorination treatment, micro-arc oxidation treatment or anodizing treatment is completed by conventional technical means in the field; the purpose of the surface treatment is to improve the bonding performance between the magnesium plate and PLA and ensure the interface strength and durability between the two.

[0032] In the present invention, the molecular weight of the polylactic acid in the polylactic acid plate is preferably ≥100 kDa, further preferably ≥110 kDa, and more preferably ≥120 kDa; the polylactic acid is preferably medical grade polylactic acid purchased from Nature Works.

[0033] In the present invention, the polylactic acid board is prepared by a casting method, and the casting method is completed by conventional technical means in the art.

[0034] In the present invention, the thickness of the laminated plate preferably decreases from the n+1th layer to the 1st layer or the 2n+1th layer, that is, the n+1th layer (the middle layer of the laminated plate) is the thickest, and as a support for mechanical properties, the thickness decreases from the middle layer to the outside.

[0035] In the present invention, the total thickness of the laminated plate is preferably ≤1.2 mm, more preferably ≤0.8 mm, and even more preferably ≤0.6 mm.

[0036] In the present invention, when n is equal to 3, the number of layers of the laminate is 7, and the thickness of the laminate preferably decreases from the 4th layer to the 1st layer or the 7th layer. Preferably, the thickness of the 2nd magnesium alloy plate and the thickness of the 6th magnesium alloy plate are independently 1 / 2 of the thickness of the 4th magnesium alloy layer, the thickness of the 3rd polylactic acid plate and the 5th polylactic acid plate are equal, the thickness of the 1st polylactic acid plate is 1 / 2 of the thickness of the 3rd polylactic acid plate, and the thickness of the 7th polylactic acid plate is 1 / 2 of the thickness of the 5th polylactic acid plate.

[0037] In the present invention, the ratio of the total thickness of the magnesium alloy plates used in the laminated plate to the total thickness of the polylactic acid plates used in the laminated plate is preferably 1:1-2, more preferably 1:1.2-1.8, and even more preferably 1:1.5-1.6.

[0038] In the present invention, the preheating temperature is preferably 110-130°C, more preferably 115-125°C, and more preferably 120°C; the preheating time is preferably 5-10 min, more preferably 6-9 min, and more preferably 7-8 min.

[0039] In the present invention, the temperature of the hot pressing treatment is preferably 150-180°C, more preferably 155-175°C, and more preferably 160-170°C; the pressure of the hot pressing treatment is preferably 3-5MPa, more preferably 3.5-4.5MPa, and more preferably 4MPa; the time of the hot pressing treatment is preferably 10-15min, more preferably 11-14min, and more preferably 12-13min.

[0040] In the present invention, after the hot pressing treatment is completed, the material is naturally cooled to room temperature to obtain a gradient structure composite material.

[0041] The present invention also provides a gradient structure composite material prepared by the preparation method of the gradient structure composite material.

[0042] The schematic diagram of the structure of the gradient structure composite material in the present invention is as follows: Figure 1 As shown; Figure 1 In the figure, 1 is a polylactic acid plate, and 2 is a magnesium alloy plate.

[0043] The invention also provides application of the gradient structure composite material in preparing oral repair materials.

[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0045] Example 1

[0046] A WE43 magnesium alloy plate (thickness 0.25 mm) was subjected to micro-arc oxidation treatment. Specifically, the WE43 magnesium alloy plate was used as the anode, the stainless steel plate was used as the cathode, and the solution obtained by mixing NaOH, Na2SiO3, Na3PO4 and water was used as the electrolyte solution (the mass concentration of the electrolyte solution NaOH was 25 g / L, the mass concentration of Na2SiO3 was 25 g / L, and the mass concentration of Na3PO4 was 5 g / L). During the treatment, a constant current mode was applied, and the battery voltage changed with the treatment time. The current density was set to 6 A / dm 2 , the power frequency is 600 Hz, the treatment time is 8 min, and the treated magnesium alloy plate is obtained; the medical polylactic acid with a molecular weight of 100 kDa is prepared into a polylactic acid plate with a thickness of 0.2 mm by a casting method;

[0047] The treated magnesium alloy plates and polylactic acid plates are alternately stacked to obtain a laminated plate with three layers (with a total thickness of 0.65 mm), wherein the first and third layers of the laminated plate are both polylactic acid plates, and the second layer is a magnesium alloy plate;

[0048] The laminate was preheated at 110°C for 8 minutes, and then hot pressed at a temperature of 175°C and a pressure of 4 MPa. The holding time of the hot pressing was set to 10 minutes. After the hot pressing treatment, it was naturally cooled to room temperature to obtain a gradient structure composite material.

[0049] Example 2

[0050] Three AZ31 magnesium alloy plates (one with a thickness of 0.25 mm and two with a thickness of 0.12 mm) were subjected to anodization treatment. Specifically, the AZ31 magnesium alloy plate was used as the anode, the stainless steel plate was used as the cathode, and the solution obtained by mixing NaOH, Na2B4O7·10H2O, Na2SiO3·9H2O, C6H8O7·H2O and water was used as the electrolyte solution (the mass concentration of the electrolyte solution NaOH was 50 g / L, the mass concentration of Na2B4O7·10H2O was 40 g / L, the mass concentration of Na2SiO3·9H2O was 60 g / L, and the mass concentration of C6H8O7·H2O was 12 g / L). During the treatment, a constant current mode was applied, and the battery voltage varied with the treatment time. The current density was set to 10 mA / cm 2 , the oxidation time is 13min, and the treated magnesium alloy plate is obtained; the medical polylactic acid with a molecular weight of 150kDa is prepared into polylactic acid plates by a casting method, two of which are 0.2mm thick and two of which are 0.1mm thick;

[0051] The treated magnesium alloy plates and polylactic acid plates are alternately stacked to obtain a laminated plate with 7 layers (with a total thickness of 1.09 mm), wherein the first, third, fifth and seventh layers of the laminated plate are all polylactic acid plates, and the second, fourth and sixth layers are all magnesium alloy plates;

[0052] The laminate was preheated at 130°C for 5 minutes, and then hot pressed at a temperature of 170°C and a pressure of 4 MPa. The holding time of the hot pressing was set to 12 minutes. After the hot pressing treatment, it was naturally cooled to room temperature to obtain a gradient structure composite material.

[0053] Example 3

[0054] Three ZK60 magnesium alloy plates (one with a thickness of 0.25 mm and two with a thickness of 0.12 mm) were subjected to fluorination treatment respectively. Specifically, the ZK60 magnesium alloy plates were immersed in a hydrofluoric acid solution with a mass fraction of 50%, and the volume ratio of the sample to the hydrofluoric acid solution was set to 1:40. The immersion time was 27 h to obtain the treated magnesium alloy plates; medical polylactic acid with a molecular weight of 150 kDa was prepared into polylactic acid plates by a casting method, two of which were 0.18 mm thick and two of which were 0.09 mm thick;

[0055] The treated magnesium alloy plates and polylactic acid plates are alternately stacked to obtain a laminated plate with 7 layers (with a total thickness of 1.03 mm), wherein the first, third, fifth and seventh layers of the laminated plate are all polylactic acid plates, and the second, fourth and sixth layers are all magnesium alloy plates;

[0056] The laminate was preheated at 120°C for 10 minutes, and then hot pressed at 160°C and 3.5 MPa. The holding time of the hot pressing was set to 15 minutes. After the hot pressing treatment, it was naturally cooled to room temperature to obtain a gradient structure composite material.

[0057] Referring to ASTM D7264-2015, the gradient structure composite materials prepared in Examples 1 to 3 were subjected to mechanical property tests to obtain bending stress-strain curves of the gradient structure composite materials in Examples 1 to 3, as shown in FIG. Figure 2 As shown. Figure 2 It can be obtained that the bending strength of the gradient structure composite material obtained in Example 1 is close to 40MPa; the gradient structure composite material obtained in Example 2 shows high bending strength and good toughness, and the bending strength reaches 71MPa. The design of the gradient structure enables the material to have different mechanical properties in different areas to adapt to the complex mechanical environment of the oral cavity; the bending strength of the gradient structure composite material obtained in Example 3 reaches 82MPa, and the hardness gradually decreases from the inner layer to the outer layer, forming a gradient hardness distribution, which effectively reduces stress concentration.

[0058] Referring to ISO 10993-12:2021, IDT Biological Evaluation of Medical Devices Part 12: Sample Preparation and Reference Materials, the gradient structured composite materials prepared in Examples 1 to 3 were subjected to biocompatibility tests, and the gradient structured composite material obtained in Example 1 was non-toxic to fibroblasts, and the cell survival rate was over 95%; the gradient structured composite material obtained in Example 2 was non-toxic to fibroblasts and had no adverse effects; the gradient structured composite material obtained in Example 3 had no adverse effects on the proliferation and differentiation of fibroblasts.

[0059] Comparative Example 1

[0060] A pure magnesium plate with a thickness of 1 mm and a commercially available PLA plate (purchased from Natureworks, model: Ingeo TM The laminated plates were combined by mechanical bonding, and the laminated plates were hot pressed at a temperature of 180°C and a pressure of 5 MPa. The holding time of the hot pressing was set to 30 min. After the hot pressing treatment, the laminated plates were naturally cooled to room temperature to obtain a composite material.

[0061] According to ASTM D7264-2015, the composite material prepared in the comparative example was subjected to a mechanical property test, and it was found that compared with the gradient structure composite material prepared in the example, the composite material prepared in the comparative example exhibited a lower flexural strength of about 30 MPa.

[0062] It can be seen from the above embodiments that the present invention provides a method for preparing a gradient structure composite material, comprising the following steps: alternately stacking magnesium alloy plates and polylactic acid plates to obtain a laminated plate; the number of layers of the laminated plate is 2n+1, n≥1 and n is an odd number; the first layer and the 2n+1 layer of the laminated plate are both polylactic acid plates, and the n+1 layer of the laminated plate is a magnesium alloy plate; the laminated plate is sequentially preheated and hot-pressed to obtain a gradient structure composite material. The present invention uses magnesium plates and PLA as raw materials, and realizes the composite of gradient structure through hot pressing process. The obtained composite material has excellent biocompatibility and mechanical properties, and is particularly suitable for the field of oral repair. In addition, the present invention achieves a good combination between magnesium plates and polylactic acid plates by precisely controlling the hot pressing conditions, and prepares a composite material with gradient mechanical properties, which provides a new material selection for oral repair.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gradient structure composite material, characterized in that: It includes the following steps: Alternately stacking magnesium alloy plates and polylactic acid plates to obtain a laminated plate; The number of layers of the laminate is 2n+1, n≥1 and n is an odd number; The first layer and the 2n+1 layer of the laminated plate are both polylactic acid plates, and the n+1 layer of the laminated plate is a magnesium alloy plate; The laminated plates are subjected to preheating treatment and hot pressing treatment in sequence to obtain the gradient structure composite material.

2. The method for preparing the gradient structure composite material according to claim 1, characterized in that: The magnesium alloy plate includes AZ31 magnesium alloy plate, ZK60 magnesium alloy plate or WE43 magnesium alloy plate.

3. The method for preparing the gradient structure composite material according to claim 1 or 2, characterized in that: The magnesium alloy plates are surface treated before lamination; the surface treatment method is fluorination treatment, micro-arc oxidation treatment or anodizing treatment.

4. The method for preparing the gradient structure composite material according to claim 3, characterized in that: The molecular weight of the polylactic acid in the polylactic acid board is ≥100kDa.

5. The method for preparing the gradient structure composite material according to claim 4, characterized in that: The thickness of the laminated plate decreases from the n+1th layer to the 1st layer or the 2n+1th layer, and the total thickness of the laminated plate is ≤1.2 mm.

6. The method for preparing the gradient structure composite material according to claim 5, characterized in that: The ratio of the total thickness of the magnesium alloy plates used in the laminated plate to the total thickness of the polylactic acid plates used in the laminated plate is 1:1-2.

7. The method for preparing the gradient structure composite material according to claim 6, characterized in that: The preheating treatment temperature is 110-130° C., and the preheating treatment time is 5-10 minutes.

8. The method for preparing the gradient structure composite material according to claim 7, characterized in that: The temperature of the hot pressing treatment is 150-180° C., the pressure of the hot pressing treatment is 3-5 MPa, and the time of the hot pressing treatment is 10-15 min.

9. A gradient structure composite material prepared by the method for preparing a gradient structure composite material according to any one of claims 1 to 8.

10. Use of the gradient structure composite material according to claim 9 in preparing oral restoration materials.

Citation Information

Cited By

  • Bionic polylactic acid-based composite material and automobile door cover connecting process

    CN121777547A